The Effect of Credit Risk, Liquidity, and Capital Structure on the Financial Performance of Conventional Banks with Profitability as a Control Variable - Maulana Fajar Satriawan; Wuryaningsih Dwi Lestari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study analyzes the effect of credit risk, liquidity, and capital structure on the financial performance of conventional banks, with profitability as a control variable. The research employs a quantitative method using panel data from conventional banks listed on the Indonesia Stock Exchange during the 2021–2024 period. The variables examined include NPL, LDR, CAR, ROE, and ROA, with testing conducted through panel data regression. The results show that credit risk has a significant positive effect, liquidity has a positive but insignificant effect, while capital structure demonstrates a negative and insignificant effect. Profitability is found to have a significant positive effect. Simultaneously, the research variables explain 74.64% of the variation in financial performance, with the remaining portion influenced by other factors. These findings emphasize that credit risk management and profitability play a crucial role in strengthening banks’ financial performance. Therefore, management should focus on risk control and profitability maintenance to enhance competitiveness and investor confidence.